Results 1 to 13 of 13
Like Tree2Thanks
  • 1 Post By dokrbb
  • 1 Post By ebaines

Math Help - Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

  1. #1
    Junior Member
    Joined
    Mar 2013
    From
    moon
    Posts
    56

    Question Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Hello

    So I tried solving this substituting x = 0 then I get f'(x) = 0.
    But that seems to be wrong.
    If I use the product law of derivatives then I get 0*(0-1)*(0-2)....=0
    Why we can't substitute x=0 first, then take the derivative of the entire expression, instead we have to first take the derivative then substitute x=0 which gives another answer...
    How to calculate this properly?

    Thanks.
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Member dokrbb's Avatar
    Joined
    Feb 2013
    From
    ...from out there ;)
    Posts
    236
    Thanks
    21

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by ryu1 View Post
    Hello

    So I tried solving this substituting x = 0 then I get f'(x) = 0.
    But that seems to be wrong.
    If I use the product law of derivatives then I get 0*(0-1)*(0-2)....=0
    Why we can't substitute x=0 first, then take the derivative of the entire expression, instead we have to first take the derivative then substitute x=0 which gives another answer...
    How to calculate this properly?

    Thanks.
    you did it wrong because you did it backward.

    You have to take the derivative of a function, and after that to find f'(0) for the derivative you got (which has to be considered as a function),

    to answer to your question Why?

    just think about what you understand by x and f(x), or x and f'(x), what's the difference between those two?

    btw, what did you obtain by blugging x=0 directly in your function f(x)?
    Thanks from ryu1
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Junior Member
    Joined
    Mar 2013
    From
    moon
    Posts
    56

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by dokrbb View Post
    you did it wrong because you did it backward.

    You have to take the derivative of a function, and after that to find f'(0) for the derivative you got (which has to be considered as a function),

    to answer to your question Why?

    just think about what you understand by x and f(x), or x and f'(x), what's the difference between those two?

    btw, what did you obtain by blugging x=0 directly in your function f(x)?
    Oh I see, i got f'(0) = 0 which is like blugging(?) x=0 directly in the function f(x). but that is wrong, which is why we first take the derivative then plunging (is that the right word? :P) the value for x=0..
    So how do you normally take the derivative of a polynomial this long
    x(x-1)(x-2)....(x-96) ? theres obviously a trick here, no one would (normally) let you manually calculate it...but I can't figure it out.
    Last edited by ryu1; April 19th 2013 at 08:40 AM.
    Follow Math Help Forum on Facebook and Google+

  4. #4
    MHF Contributor ebaines's Avatar
    Joined
    Jun 2008
    From
    Illinois
    Posts
    1,096
    Thanks
    317

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    You don't need to find the general form of f'(x), you only need to find f'(0). The function f(x) is a big polynomial, of order x^97:

    f(x) = x(x-1)(x-2)...(x-96) = x^(97) + Ax^(96) + Bx^(95) + .... + Wx^3 + Yx^2 + Zx

    where the A, B, etc terms are constants. Its derivative is also a polynomial, of order one less than the original polynomial:

    f'(x) = 97x^(96) + 96Ax^(95) + 95Bx^(94) + ... + 3Wx^2 + 2Yx + Z

    Note that at x=0 all these terms equal zero except for the last, so you have f'(0) = Z. Now the only thing left to do is figure out the value of Z, which is the coefficient of the x^1 term in the original polynomial. I'll leave that to you!
    Last edited by ebaines; April 19th 2013 at 09:28 AM.
    Thanks from ryu1
    Follow Math Help Forum on Facebook and Google+

  5. #5
    Junior Member
    Joined
    Mar 2013
    From
    moon
    Posts
    56

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by ebaines View Post
    You don't need to find the general form of f'(x), you only need to find f'(0). The function f(x) is a big polynomial, of order x^97:

    f(x) = x(x-1)(x-2)...(x-96) = x^(97) + Ax^(96) + Bx^(95) + .... + Wx^3 + Yx^2 + Zx

    where the A, B, etc terms are constants. Its derivative is also a polynomial, of order one less than the original polynomial:

    f'(x) = 97x^(96) + 96Ax^(95) + 95Bx^(94) + ... + 3Wx^2 + 2Yx + Z

    Note that at x=0 all these terms equal zero except for the last, so you have f'(0) = Z. Now the only thing left to do is figure out the value of Z, which is the coefficient of the x^1 term in the original polynomial. I'll leave that to you!
    I get something crazy like -1*-2*-3...*-96
    Is that right?
    I think it's called factorial 96! ?
    I read we can't calculate the factorial of negative numbers but (we can say it's positive because it's an even number therefore -96! = 96! ?)


    Thanks.
    Last edited by ryu1; April 19th 2013 at 02:51 PM.
    Follow Math Help Forum on Facebook and Google+

  6. #6
    MHF Contributor

    Joined
    Aug 2006
    Posts
    18,665
    Thanks
    1616
    Awards
    1

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by ryu1 View Post
    I get something crazy like -1*-2*-3...*-96
    Is that right?
    I think it's called factorial 96! ?
    I read we can't calculate the factorial of negative numbers but (we can say it's positive because it's an even number therefore -96! = 96! ?)
    This question can be done using logarithmic differentiation. But I suggest doing a simple example.

    Let f(x)=x(x-1)(x-2) then f'(x)=(x-1)(x-2)+x(x-2)+x(x-1). Is that correct?

    If so is it clear that f'(0)=2~?

    Isn't easy to generalize?



    Post Script

    f(x) = \prod\limits_{k = 0}^{96} {\left( {x - k} \right)}

    f'(x) = \sum\limits_{j = 0}^{96} {\left( {\prod\limits_{k = 0,k \ne j}^{96} {\left( {x - k} \right)} } \right)}

    f'(0)=~?
    Last edited by Plato; April 19th 2013 at 03:47 PM.
    Follow Math Help Forum on Facebook and Google+

  7. #7
    Member
    Joined
    Jan 2009
    Posts
    153

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    f'(x)=\prod_{i=1}^{96}(x-i)+x\left[\prod_{i=2}^{96}(x-i)+(x-1)\prod_{i=2}^{96}(x-i)+\cdots\right]\rightarrow f'(0)=\prod_{i=1}^{96}(-i)=96!
    Follow Math Help Forum on Facebook and Google+

  8. #8
    MHF Contributor

    Joined
    Aug 2006
    Posts
    18,665
    Thanks
    1616
    Awards
    1

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by math2009 View Post
    f'(x)=\prod_{i=1}^{96}(x-i)+x\left[\prod_{i=2}^{96}(x-i)+(x-1)\prod_{i=2}^{96}(x-i)+\cdots\right]\rightarrow f'(0)=\prod_{i=1}^{96}(-i)=96!
    So well, How does that help? Our object is to help? learning?
    Follow Math Help Forum on Facebook and Google+

  9. #9
    Junior Member
    Joined
    Mar 2013
    From
    moon
    Posts
    56

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by Plato View Post
    This question can be done using logarithmic differentiation. But I suggest doing a simple example.

    Let f(x)=x(x-1)(x-2) then f'(x)=(x-1)(x-2)+x(x-2)+x(x-1). Is that correct?

    If so is it clear that f'(0)=2~?

    Isn't easy to generalize?



    Post Script

    f(x) = \prod\limits_{k = 0}^{96} {\left( {x - k} \right)}

    f'(x) = \sum\limits_{j = 0}^{96} {\left( {\prod\limits_{k = 0,k \ne j}^{96} {\left( {x - k} \right)} } \right)}

    f'(0)=~?
    yes f'(0) = 2 in that case.
    so if i have x(x-1)(x-2)...(x-n) f'(0) = n ? or n! ?
    But I got 96! thing.

    I have no idea what those big E and big pi thing operators mean yet.
    Follow Math Help Forum on Facebook and Google+

  10. #10
    MHF Contributor

    Joined
    Aug 2006
    Posts
    18,665
    Thanks
    1616
    Awards
    1

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by ryu1 View Post
    yes f'(0) = 2 in that case.
    so if i have x(x-1)(x-2)...(x-n) f'(0) = n ? or n! ?
    But I got 96! thing.

    I have no idea what those big E and big pi thing operators mean yet.

    In this case I must ask why in the world were yo you given this question? Frankly if I were you, I would complain loudly to your educational authority. It seems to be that your instructor is of bass on this one. You can use this post if you want.
    Follow Math Help Forum on Facebook and Google+

  11. #11
    Junior Member
    Joined
    Jan 2011
    Posts
    71

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    You could accost somebody at your school, or you could take another look at posts 4 and 5. Do some simpler examples. Let f(x)=x(x-1). Expand this and then take the derivative (as ebaines said, you really only need to know one term of f(x) to find f'(0)). Now let f(x)=x(x-1)(x-2). Expand this and then take the derivative. If you keep going and do this one more time, you should answer your n or n! question.
    Follow Math Help Forum on Facebook and Google+

  12. #12
    Junior Member
    Joined
    Mar 2013
    From
    moon
    Posts
    56

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by Plato View Post
    In this case I must ask why in the world were yo you given this question? Frankly if I were you, I would complain loudly to your educational authority. It seems to be that your instructor is of bass on this one. You can use this post if you want.
    it is meant to practice only the derivative function.

    someone offered to to do this

    let g(x) = (x-1)(x-2)...(x-96)
    let f(x) = xg(x)
    f'(x) = xg'(x) + g(x)*1
    f'(0) = 0g'(0) + 1g(0)
    g(0) = (-1)(-2)...(-96)

    does that work?

    Thanks again.
    Follow Math Help Forum on Facebook and Google+

  13. #13
    MHF Contributor ebaines's Avatar
    Joined
    Jun 2008
    From
    Illinois
    Posts
    1,096
    Thanks
    317

    Re: Derivative f'(0) for f(x) =x*(x-1)(x-2)....(x-96)

    Quote Originally Posted by ryu1 View Post
    does that work?

    Thanks again.
    Yes that works - it's an interesting technique. So now you have two approaches that both give the same answer!

    Quote Originally Posted by Plato
    In this case I must ask why in the world were yo you given this question? Frankly if I were you, I would complain loudly to your educational authority. It seems to be that your instructor is of bass on this one. You can use this post if you want.
    I don't see the issue, as there are at least two ways to solve this without employing symbology that many college freshmen or seniors in highschool have not been exposed to. I'm referring here specifically to the use of the product operator; admittedly the OP should be familiar with the summation symbol - he must have been asleep in class when they covered that topic.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Replies: 4
    Last Post: October 17th 2012, 06:51 AM
  2. contuous weak derivative $\Rightarrow$ classic derivative ?
    Posted in the Differential Geometry Forum
    Replies: 2
    Last Post: April 22nd 2011, 02:37 AM
  3. Replies: 0
    Last Post: January 24th 2011, 11:40 AM
  4. Replies: 2
    Last Post: November 6th 2009, 02:51 PM
  5. Replies: 1
    Last Post: January 7th 2009, 01:59 PM

Search Tags


/mathhelpforum @mathhelpforum